2019
DOI: 10.3389/fpsyg.2019.01339
|View full text |Cite
|
Sign up to set email alerts
|

The Validity and Reliability of Live Football Match Statistics From Champdas Master Match Analysis System

Abstract: The aim of the present study was to investigate the validity of match variables and the reliability of Champdas Master System used by trained operators in live association football match. Twenty professional football coaches voluntarily participated in the validation of match variables used in the System. Four well-trained operators divided into two groups that independently analyzed a match of Spanish La Liga. The Aiken’s V averaged at 0.84 ± 0.03 and 0.85 ± 0.03 for the validation of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Technical performance data were collected from the website of Champion, 1 a leading Chinese sport data company. The validity and reliability of the Champdas Master Match Analysis System was verified by Gong et al (2019), who demonstrated that Aiken's V averaged 0.84 ± 0.03 and 0.85 ± 0.03 for the validation of indicators. Moreover, high kappa values (Operator 1: 0.92 and 0.90; Operator 2: 0.91 and 0.88), high intraclass correlation coefficients (varied from 0.93 to 1.00), and low standardized typical errors (varied from 0.01 to 0.34) indicated a high level of intraoperator reliability.…”
Section: Data Sources and Reliabilitymentioning
confidence: 96%
“…Technical performance data were collected from the website of Champion, 1 a leading Chinese sport data company. The validity and reliability of the Champdas Master Match Analysis System was verified by Gong et al (2019), who demonstrated that Aiken's V averaged 0.84 ± 0.03 and 0.85 ± 0.03 for the validation of indicators. Moreover, high kappa values (Operator 1: 0.92 and 0.90; Operator 2: 0.91 and 0.88), high intraclass correlation coefficients (varied from 0.93 to 1.00), and low standardized typical errors (varied from 0.01 to 0.34) indicated a high level of intraoperator reliability.…”
Section: Data Sources and Reliabilitymentioning
confidence: 96%
“…The inter-player passing statistics of all matches were tracked and provided by the Shanghai Champion Information Technology Co., Ltd. through a validated data collection system (Champdas Master System, http://www.champdas.com) operated by trained collectors, and they have at least two years of experience in operating the system. 3 The starting players and substitutes were all included. However, as the study only considered the passing performance of outfield players when teams were in possession of the ball, after organising the data, any inter-player passing count less than five passes was ruled out, and goalkeeper-involved passes were also excluded during the filtering process.…”
Section: Methodsmentioning
confidence: 99%
“…Computer-based approaches have been applied to collect and analyse technical, tactical and physical aspects in team sport, especially in football, and progressively increased the information and dimensions related to the study of match performance behaviours. 13 Recently, the general structure of football teams and connections among players during match-play were investigated using social network analysis (SNA). 47 Contrast to the traditional notational analysis, the SNA considers and models passing distribution of teams and is proved to be useful since its concepts and methods could not only illuminate player’s or team’s dynamics, but also improve the understanding of complex relational interactions within the team.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 26 performance indicators related to goal-scoring, defending and organizing (see Table 1) were extracted from the data based on the previous related studies, which showed that these indicators were highly related with match outcome (Gong et al, 2019;Goumas, 2014;. Effect of tournament format change on team performance of Chinese Football Super League during COVID-19 pandemic.…”
Section: Devicesmentioning
confidence: 99%